2003
DOI: 10.1091/mbc.e02-06-0315
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4 Recycles via atrans-Golgi Network (TGN) Subdomain Enriched in Syntaxins 6 and 16 But Not TGN38: Involvement of an Acidic Targeting Motif

Abstract: Insulin stimulates glucose transport in fat and muscle cells by triggering exocytosis of the glucose transporter GLUT4. To define the intracellular trafficking of GLUT4, we have studied the internalization of an epitope-tagged version of GLUT4 from the cell surface. GLUT4 rapidly traversed the endosomal system en route to a perinuclear location. This perinuclear GLUT4 compartment did not colocalize with endosomal markers (endosomal antigen 1 protein, transferrin) or TGN38, but showed significant overlap with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
237
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 194 publications
(262 citation statements)
references
References 56 publications
25
237
0
Order By: Relevance
“…To further determine the relationship of GLUT4 and p115, we compared the localization of the latter to the Golgi proteins, syntaxin6 and GM130, as shown in Figure 5B. These three proteins overlap to a much greater extent than do p115 and Glut4, consistent with previous data (Shewan et al, 2003).…”
Section: Characterization Of P115 Localization and Function By Immunosupporting
confidence: 83%
See 3 more Smart Citations
“…To further determine the relationship of GLUT4 and p115, we compared the localization of the latter to the Golgi proteins, syntaxin6 and GM130, as shown in Figure 5B. These three proteins overlap to a much greater extent than do p115 and Glut4, consistent with previous data (Shewan et al, 2003).…”
Section: Characterization Of P115 Localization and Function By Immunosupporting
confidence: 83%
“…To further determine the relationship of GLUT4 and p115, we compared the localization of the latter to the Golgi proteins, syntaxin6 and GM130, as shown in Figure 5B. These three proteins overlap to a much greater extent than do p115 and Glut4, consistent with previous data (Shewan et al, 2003).To determine if this p115-GSV colocalization has functional significance, we used electroporation to overexpress the N-and C-terminal p115 constructs described in Figure 4 that we fused to EGFP for reporting their presence by immunofluorescence. We show that the electroporation procedure itself, using EGFP expression alone, does not affect endogenous GLUT4 trafficking (Figure 6, A and B).…”
supporting
confidence: 84%
See 2 more Smart Citations
“…Subsequently GLUT4 becomes sequestered from these compartments and equilibrates with the remaining GLUT4 protein in the IRC [38]. It has also been suggested that GLUT4 may not necessary directly traffic back to the IRC but may re-enter into the Golgi/TGN secretory system and then undergo sorting to the IRC [102]. Although the sorting proteins involved in these processes have only been poorly defined, the adaptor protein 2 (AP2) complex is required for the plasma membrane sorting into clathrin-coated pits [103,104].…”
Section: Glut4 Endocytosismentioning
confidence: 99%